Relatos e percepções de um grupo de mulheres fibromiálgicas: estratégias para a promoção de saúde - Barboza, Marcelo Alves (2010)
Introduction: Fibromyalgia is considered a non-articular rheumatic syndrome of unknown origin, characterized by widespread pain, fatigue and remissive algic patient‟s condition. The persistent chronic pain, associated with somatic and psychosocial changes, intensifies the suffering in the face of the syndrome, and negatively affects the quality of life and also the personal, social and familial relationships. Objectives: To analyze stories and perceptions of a group of women with fibromyalgia inserted in a multiprofessional group, valuing the experiences collected as strategy for promoting health and quality of life. Methods: The study was conducted in the city of Araxá – MG, Clinic-School of Physiotherapy UNIARAXÁ, being approved by the Ethics in Research of UNIFRAN. Study participants were 11 women, aged 25-60 years. To include participants, two criterions were taken into consideration: clinical diagnosis of fibromyalgia, according to the criteria of the American College of Rheumatology, and cognitive ability to respond to questionnaires. Two instruments were used in this study: the SF-36 questionnaire, to evaluate the quality of life, and the semi-structured questionnaire, to collect participants‟ reports and perceptions in the face of fibromyalgia. The instruments were applied at the beginning of the study and after 11 months, at the end of the group activities. The group meetings were held collectively, three times a week lasting 50 minutes. Results: From the initial data, low scores were noted in the domains of the SF-36 questionnaire, which can be translated into loss in the domains that evaluate the quality of life and negative implications of fibromyalgia in activities of routine, social and familial relationships, described in the semi-structured questionnaire. At the end of this study, better scores were found in all domains of the SF-36, interpreted as an improvement in the perception of the quality of life, and stories that considered the working group has helped as a positive experience for addressing the chronic condition of fibromyalgia.